Avoid the “Pitfalls”: Specific Features of Organizational Change Governance - Vladimirovna, Korsakova Tatiana (Journal of Ecohumanism, 2024)
The exponential growth of technology contrasts with the slower linear relationships of organizational growth. In the face of constant changes in the world, it is important to understand whether an organization is ready to implement innovative ideas, since otherwise this will not increase its creativity and competitiveness. However, many organizations today are exactly the same as they were in the previous days. This situation mainly concerns the practice of interaction and change management. This means that the organization must be able to realize its potential at the same speed as new opportunities appear in the world. This empirical study is aimed at managing change in an organization, as well as addressing the question of how to act so that the implemented changes are comfortable, appropriate, useful and take root; how to ensure that a smart idea is executed well and ultimately delivers value. The real situation is researched from an observational point of view. An empirical model for managing organizational change in conditions of intense changes in the eco-environment and human nature itself is presented.